Plants, a Yardstick for Measuring the Environmental Consequences of the Cretaceous-Tertiary Boundary Event - Sweet, A. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2001)
Summary Reactions registered by plant communities to the Cretaceous-Tertiary (K-T) boundary cometary impact event include extinctions, killing events, shifts in the relative number and abundances of taxa, and, for some taxa, an apparent insensitiviry to imposed stresses. All these provide yardsticks to measure the extent of impact-generated environmental perturbations: extinctions by their magnitude and selectiveness, killing events by their geographic extent, and the survivors by their varying sensitivities to the boundary event as reflected in trends in their relative abundances and distribution. Information has been assembled from localities in western Canada and Montana thatsuggests: most plant extinctions involvedwhat were likely zoophilous (animal-pollinated) angiosperms; under story vegetation may have survived the event; there was extensive destruction of the forest canopy on a continental scale; and there was a variable response to the K-T boundary event by what were likely wind-pollinated angiosperms.